GAMBARAN TINGKAT KECEMASAN DALAM MENGHADAPI UJI KOMPETENSI PADA MAHASISWA/I TINGKAT AKHIR DIPLOMA III KEPERAWATAN FAKULTAS KEDOKTERAN UNIVERSITAS ABULYATAMA - Edhitta Deviani; Sumarni Sumarni (Jurnal Sains Riset, 2020)
Competency test is an assessment of student learning outcomes in the health sector. The competency test is divided into two stages, namely the written test and the practical test. Based on the Circular issued by the Directorate General of Higher Education, the competency test will be carried out at the final stage after completing all stages of education as an exit exam where the formulation must pay attention to the importance of a professional academic environment as an ability qualification test. Anxiety during the competency test is a problem that can negatively affect the results of the competency test. The results of a research study on the Description of Anxiety Levels in Facing Competency Tests in Final Level Students of Diploma III Nursing, Faculty of Medicine, Abulyatama University. In this study using a descriptive design with a cross sectional method with a sample of 30 respondents consisting of all final year students by using the HARS questionnaire (Hamilton anxiety rating scale) in the form of a google form which was carried out in the Diploma III Nursing Study Program, Faculty of Medicine, Abulyatama University with the results Research on 30 respondents showed that the highest level of anxiety was in the category of mild anxiety as many as 24 respondents (80%). Students' Anxiety Levels in Facing Competency Tests in terms of the Grade Point Average (GPA). A total of 19 respondents (63.3%) got a very satisfactory GPA. Anxiety Levels of Students in Facing Competency Tests in terms of gender from the number of 9 male respondents only 1 person experienced moderate anxiety, while 4 women (13.3%) experienced moderate anxiety from the number of respondents 21 people. It is hoped that after knowing the respondent's anxiety level, they can further increase their knowledge by frequentlyparticipating in training for example competency test questions. And for nursing education,it is hoped that it can be input for educators in preparing questions that support the level of achievement of competency test graduates very satisfactorily.Keywords: Anxiety, Competency Test, Final Year Students